Development of small and medium-sized enterprise horizontal innovation networks: UK agri-food sector study. (November 2014) - McAdam, Maura; McAdam, Rodney; Dunn, Adele; McCall, Clare
Within the management literature, there is an emergent discourse on horizontal collaboration among small and medium-sized enterprises (SMEs), whereby individual rivalries are overcome by the need for more resources and innovation, leading to increased competitiveness through joint product development. In particular, a number of these horizontal collaborations between SMEs have occurred within the agri-food sector. As a consequence, this article aims to explore the longitudinal development of horizontal innovation networks within an artisan bakers' network as part of the UK SME agri-food sector. An interpretivist research approach was used, whereby the development and evolution of an artisan bakers' horizontal network was studied over a 27-month period. The findings, as summarised in conceptual models which draw upon knowledge-based open innovation and social network constructs, illustrate that a complex three-stage life cycle development occurred within the bakers' horizontal network.